Prevalence and Determinants of Significant Liver Fibrosis by Vibration-Controlled Transient Elastography in Thai Chronic Hepatitis B Patients - Apichet Sirinawasatien; Thanaya Techasirioangkun; Siriporn Thongsri (International Journal of Hepatology)
Aims. To describe the prevalence of significant liver fibrosis by ultrasound-based vibration-controlled transient elastography (VCTE; FibroScan®) and to identify the determinants of significant liver fibrosis in Thai chronic hepatitis B patients. Methods. A cross-sectional study of consecutive chronic hepatitis B patients performed VCTE and followed up at Rajavithi Hospital, Bangkok, Thailand, was conducted between 1 January, 2013, and 31 December, 2016. Liver fibrosis was defined as minimal (METAVIR F0-1) by VCTE < 7.2 kPa and significant (METAVIR F2-4) by VCTE ≥ 7.2 kPa. VCTE assessments and medical records were retrospectively reviewed. The prevalence and determinants of significant liver fibrosis were analyzed. Results. A total of 206 eligible patients were included; 120 patients (58.3%) were female. The mean age was 50 years (SD 12.4 years), and 32.5% had a body mass index ≥ 25. The prevalences of minimal (F 0-1) and significant fibrosis (F2-4) were 74.3% and 25.7%, respectively. The prevalence of hepatitis B e antigen negative (HBeAg -ve) was 83%. The median serum hepatitis B virus viral load was 4,340 IU/mL (range 20-271,883,036). Significant determinants of significant fibrosis (F2-4) were male gender (aOR 3.24 [95%CI: 1.36-7.72]) and high aspartate transaminase (AST) level (aOR 5.71 [95%CI: 2.03-16.04]). Conclusion. Around one-quarter of the Thai patients with chronic viral hepatitis B had significant liver disease defined by VCTE, requiring further evaluation for specific treatment for hepatitis B virus. Determinants of significant liver fibrosis were male gender and high AST level.